Integration of adequate work facilities and high work discipline in optimizing employee performance at PT Bintang Krakatau Mandiri Cilegon-Banten - Suheri Suheri; Didit Haryadi; Sri Mulyati; Fadjar Muliawan; Ela Susila; Syaechurodji Syaechurodji (Institute of Accounting Research and Novation (IARN), 2025)
A company’s success is inseparable from the employee performance factor in the company. Good performance can increase productivity and operational efficiency and help the company achieve its strategic goals. This study aims to determine the aspects of improving employee performance with work facilities and work discipline. This study uses a quantitative method with probability and simple random sampling techniques. This study uses a survey method and a questionnaire tool. The number of respondents is 60. Data processing and analysis techniques use validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, correlation tests, hypothesis tests, and determination coefficient tests. The study results indicate that the work facility variable significantly affects employee performance. The work discipline variable significantly affects employee performance. The work facility and work discipline variables significantly affect employee performance. The results of this study provide insight and contribution to management science, especially human resources.